2014
DOI: 10.1038/npp.2014.268
|View full text |Cite|
|
Sign up to set email alerts
|

PPARγ Activation Attenuates Opioid Consumption and Modulates Mesolimbic Dopamine Transmission

Abstract: PPARγ is one of the three isoforms identified for the peroxisome proliferator-activated receptors (PPARs) and is the receptor for the thiazolidinedione class of anti-diabetic medications including pioglitazone. PPARγ has been long studied for its role in adipogenesis and glucose metabolism, but the discovery of the localization in ventral tegmental area (VTA) neurons opens new vistas for a potential role in the regulation of reward processing and motivated behavior in drug addiction. Here, we demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 53 publications
3
86
0
Order By: Relevance
“…PPARγ is expressed primarily in microglia and PPARγ agonists inhibit the expression of proinflammatory cytokines (Kielian and Drew, 2003). Recent studies show that stimulation of PPARγ reduces heroin self-administration and reinstatement of heroin seeking (de Guglielmo et al, 2016, 2015). …”
Section: Drugs Of Abuse and Glial Cell Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…PPARγ is expressed primarily in microglia and PPARγ agonists inhibit the expression of proinflammatory cytokines (Kielian and Drew, 2003). Recent studies show that stimulation of PPARγ reduces heroin self-administration and reinstatement of heroin seeking (de Guglielmo et al, 2016, 2015). …”
Section: Drugs Of Abuse and Glial Cell Activitymentioning
confidence: 99%
“…Interest in PPARγ agonists has grown in many neuroinflammatory disorders due to the expression of PPARγ primarily in microglia and the ability of PPARγ agonists to inhibit the expression of cytokines by monocytes/macrophages and microglia (Kielian and Drew, 2003). In response to the promising preclinical research (de Guglielmo et al, 2016, 2015), researchers sought to test the ability of PIO to alter the abuse potential of opioids in human subjects. One of these trials maintained non-dependent prescription opioid abusers (n=17 completers) on an ascending daily dose of PIO (0 mg, 15 mg, 45 mg) for 2–3 weeks per dose.…”
Section: Drugs Of Abuse and Glial Cell Activitymentioning
confidence: 99%
“…PPARγ agonists, like PIO, inhibit the expression of cytokines by monocytes/macrophages and microglia (Kielian and Drew, 2003). Preclinical research has also shown that PIO attenuates drug-induced dopamine release in the nucleus accumbens, which is an important system in the development and maintenance of addiction (Di Chiara and Bassareo, 2007; Diana, 2011; de Guglielmo et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…For instance, PPARα and PPARγ are expressed in addiction-related brain areas, such as the lateral hypothalamus and the ventral tegmental area (VTA), from which dopamine (DA) release into the NAc can be modulated (Moreno et al, 2004; Sarruf et al, 2009; Melis et al, 2010; de Guglielmo et al, 2015b). In fact, electrophysiological experiments have shown that the activation of PPARα by fibrates decreased the ability of nicotine to enhance the firing rate of VTA DA neurons.…”
Section: Peroxisome Proliferating Activator Receptors (Ppars)mentioning
confidence: 99%